Differential Gene Expression Analysis of the Epacromius coerulipes (Orthoptera: Acrididae) Transcriptome. Issue 1 (2nd May 2016) - Jin, Yongling; Cong, Bin; Wang, Liyan; Gao, Yugang; Zhang, Haiyan; Dong, Hui; Lin, Zhiwei
Abstract: Epacromius coerulipes (Ivanov) is one of the most widely distributed locusts. To date, the main methods to kill locusts still rely on chemical controls, which can result in the selection of locusts with resistance to chemical pesticides. Butene-fipronil is a new pesticide that was discovered by the structural modification of fipronil. This pesticide has been used to control various agricultural pests and has become an important pesticide product to control pests that exhibit resistance to other pesticides, including locusts. To extend its useful half-life, studies of the initiation and progression of resistance to this pesticide are needed. Herein, two E. coerulipes strains, a pesticide-sensitive (PS) and a pesticide-resistant (PR) strain, were chosen to undergo de novo assembly by paired-end transcriptome Illumina sequencing. Overall, 63, 033 unigenes were detected; the average gene length was 772 bp and the N50 was 1, 589 bp. Among these unigenes, ∼25, 132 (39.87% of the total) could be identified as known proteins in bioinformatic databases from national centers. A comparison of the PR and PS strains revealed that 2, 568 genes were differentially expressed, including 1, 646 and 922 genes that were up- and down-regulated, respectively. According to the Gene Ontology (GO) database, among biological processes the metabolic process group was the largest group (6, 900 genes, 22.47%) and contained a high frequency of differentially expressed genes (544 genes, 27.54%). According to the Clusters of Orthologous Groups (COG) categories, 28 genes, representing 2.98% of all genes, belonged to the group of genes involved in the biosynthesis, transportation, and catabolism of secondary metabolites. The differentially expressed genes that we identified are involved in 50 metabolic pathways. Among these pathways, the metabolism pathway was the most represented. After enrichment analysis of differential gene expression pathways, six pathways—ribosome; starch, and sucrose metabolism; ascorbate and aldarate metabolism; drug metabolism-cytochrome P450; metabolism of xenobiotics by cytochrome P450; and glutathione metabolism—showed a high degree of enrichment. Among these pathways, drug metabolism-cytochrome P450, metabolism of xenobiotics by cytochrome P450, and glutathione metabolism have been associated with pesticide metabolism. Furthermore, 316 unigenes in the E. coerulipes transcriptome encode detoxifying enzymes and 76 unigenes encode target proteins of pesticides. Among these genes, 23 genes that encode detoxifying enzymes in the resistance group were found to be up-regulated. The transcriptome sequencing results of E. coerulipes established a genomics database of E. coerulipes for the first time. This study also establishes a molecular basis for gene function analysis of E. coerulipes . Moreover, it provides a theoretical resource for mechanistic studies on pesticide resistance through the screening and investigation of resistance genes.